2005
DOI: 10.14295/ras.v19i2.8223
|View full text |Cite
|
Sign up to set email alerts
|

Determinação da condutividade hidráulica da Formação Rio Claro: Análise comparativa através de análise granulométrica e ensaios Com permeâmetro guelph e testes de slug

Abstract: Recebido em 25/06/2004, aceito em 11/07/2005 RESUMO A exploração de água subterrânea no município de Rio Claro ocorre predominantemente no aqüífero Itararé que, além de se situar a profundidades superiores a 150 m, possui baixa produtividade. Devido a esses fatores e ao aumento da necessidade de abastecimento na região, diversas indústrias vêm explorando água do aqüífero Rio Claro, representado pelos arenitos cenozóicos da Formação Rio Claro, cujo potencial e características hidráulicas são pouco conhecidas. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
1
7
0
3
Order By: Relevance
“…As confirmed by the results from the other measurements (geophysics; soil flux accumulation chambers) described elsewhere in this issue [12,13],which also recorded peak measurements, the highest atmospheric concentrations (maximum leakages) were registered on September 21 st , with peak concentration of approximately 1200 ppmV and isotopic ratio of -25 ppmil. These numbers seem to confirm a perturbation likely to be derived from our controlled leakage experiment, but also indicated that there was considerable dilution due to the atmospheric air.…”
Section: Eddy Covariance Measurements For Co 2 Atmospheric Fluxes Andsupporting
confidence: 82%
See 2 more Smart Citations
“…As confirmed by the results from the other measurements (geophysics; soil flux accumulation chambers) described elsewhere in this issue [12,13],which also recorded peak measurements, the highest atmospheric concentrations (maximum leakages) were registered on September 21 st , with peak concentration of approximately 1200 ppmV and isotopic ratio of -25 ppmil. These numbers seem to confirm a perturbation likely to be derived from our controlled leakage experiment, but also indicated that there was considerable dilution due to the atmospheric air.…”
Section: Eddy Covariance Measurements For Co 2 Atmospheric Fluxes Andsupporting
confidence: 82%
“…Studies of the CO 2 -bound biological stress, as indicated by the phytophysiognomy of the local vegetation as well as spectral characterization measurements, were also carried out on the field, thus providing the initial basis for botanic stress indicators (collaboration among UFSC, PUC and INPENational Institute on Spatial Research). Additional and more detailed information can be found at [13], covering specific features of the research undertaken at the site.…”
Section: Florianópolismentioning
confidence: 99%
See 1 more Smart Citation
“…A área de estudo para a realização das simulações foi o Campus da UNESP de Rio Claro (Figura 1), onde anteriormente foi conduzida a caracterização hidrogeológica conduzida por diversos trabalhos, incluindo Oliva et al (2005), Oliva (2006), Neto et al (2016) e Gonçalves & Chang (2018 Em razão da disponibilidade de oxigênio no aquífero, inicialmente o etanol é degradado por biodegradação aeróbica (Equação 1), tendo em vista que esta representa a reação termodinamicamente mais favorável.…”
Section: Materiais E Métodosunclassified
“…Neste teste é aplicada uma carga ou descarga através da introdução ou remoção súbita de um sólido de volume conhecido dentro do poço (Figura 11), de forma que o nível de água seja elevado ou rebaixado. Quando o volume é adicionado, o teste é conhecido como "slug test", caso contrário é chamado "bail test" (OLIVA; CHANG; CAETANO-CHANG, 2005). A partir do monitoramento do ní-vel de água no poço, é obtido uma curva de rebaixamento ou recuperação, com o tempo.…”
Section: Métodos Hidráulicosunclassified